Normas Voluntárias de Sustentabilidade (NVS) e implicaç\~oes sobre as exportaç\~oes de produtos do agronegócio: ALGOD\~AO - Fernanda Aparecida Silva; Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective of this study is to verify the advantages and challenges of increasing certified cotton production and to analyze whether meeting the certification requirements guarantees Brazil access to the world market. As a way of answering these questions, data on the cotton production chain are initially presented, highlighting production costs, world and national production and, finally, the commercialization of cotton (exports and domestic market). Subsequently, we sought to gather information on requirements and steps for the certification of Responsible Brazilian Cotton (ABR) and the Better Cotton Initiative (BCI). In the last phase of the research, the results obtained from contact with producers and the association of cotton producers were presented, which highlighted costs, difficulties and benefits (direct and indirect) of certification. The results obtained indicate that even without certification access to international markets is not compromised. This can be explained by the fact that the main buyers, especially Asians, still have little demand for the certified product. But what is expected is a growth trend in the coming years for Brazilian cotton with sustainability standards. On the other hand, the organization of farms, both in terms of improving rural buildings as well as attention to labor and environmental legislation, which are fundamental for receiving the ABR and BCI seal, work as a good tool to improve property management. .From the results found, it is evident that the development of a national seal, the ABR, and the benchmarking with the BCI make cotton production a successful example to be followed by the other sectors in terms of certification.
Keywords: F18; F13; Q17; 330; cotton; voluntary sustainability standards (VSS); certification; export